Volume 3: Heat Transfer; Electric Power 1981
DOI: 10.1115/81-gt-77
|View full text |Cite
|
Sign up to set email alerts
|

Streamwise Flow and Heat Transfer Distributions for Jet Array Impingement With Crossflow

Abstract: Two-dimensional arrays of circular jets of air impinging on a heat transfer surface parallel to the jet orifice plate are considered. The air, after inpingement, is constrained to exit in a single direction along the channel formed by the surface and the jet plate. The downstream jets are subjected to a crossflow originating from the upstream jets. Experimental and theoretical results obtained for streamwise distributions of jet and crossflow velocities are presented and compared. Measured Nusselt numbers reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
108
2

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(120 citation statements)
references
References 8 publications
10
108
2
Order By: Relevance
“…Florschuetz [3,4] pointed out that inline jet arrays typically performed better than the corresponding staggered arrays in terms of average heat transfer rates, because in a given streamwise row jets tended to be protected from the oncoming crossflow by the upstream jets. In the review on the heat transfer characteristics of multiple impinging air jets presented by Weigand and Spring [1], the optimum values for open area, which is defined as the ratio of jet hole area to opposing heat transfer surface area, was suggested to be 1e3%, which was basically equivalent to the jet-to-jet spacing at 4e6 jet diameters.…”
Section: Introductionmentioning
confidence: 99%
“…Florschuetz [3,4] pointed out that inline jet arrays typically performed better than the corresponding staggered arrays in terms of average heat transfer rates, because in a given streamwise row jets tended to be protected from the oncoming crossflow by the upstream jets. In the review on the heat transfer characteristics of multiple impinging air jets presented by Weigand and Spring [1], the optimum values for open area, which is defined as the ratio of jet hole area to opposing heat transfer surface area, was suggested to be 1e3%, which was basically equivalent to the jet-to-jet spacing at 4e6 jet diameters.…”
Section: Introductionmentioning
confidence: 99%
“…Kercher and Tabakoff [7], Chance [8], Metzger et al [9], Florschuetz et al [10][11][12][13] studied streamwise distributions of segment averaged Nusselt numbers. But the spanwise variations of heat transfer coefficients were not captured due to the limitations of the apparatus and technique used.…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies of jet impingements heat transfer including the effect of cross-flow were conducted by Florschutz et al [10][11][12]. Florschuetz [13] found that increasing the ratio between the imposed cross-flow mass flow rate and impingement jet flow rate from 0.2 to 0.4 could significantly reduce Nusselt number by a factor greater than 2.5.…”
Section: Introductionmentioning
confidence: 99%